Harmonising metalworking fluid formulations with end-of-life biological treatment - Uapipatanakul, B (2015)
Metalworking fluids (MWFs) are coolants and lubricants, which are widely employed in metal cutting works. They are designed to be a long lasting product. Manufacturers have designed MWFs with lack of awareness of end-of-life disposal by including biocides, which make biological treatment challenging. Here, Syntilo 9913 was used as a case study to develop a cradle-to-grave product that was biologically stable in use but amenable to sustainable hybrid biological treatment at end-of-life. The product was reverse engineered employing factorial design approach based on a priori knowledge of the product components. From the combinatorial work, it was observed that chemical interactions can results in synergistic and antagonistic effects in terms of the toxicity and biodegradability. One of the major components of most MWFs are amines such as Triethanolamine (TEA). TEA does not biodeteriorate in single compound screening, but in combination with many other components TEA was found to cause "softening" of MWF formulations. Octylamine was found to be best for "bio-hardening" but it was not economically sustainable. Hence, the modified biocide-free synthetic MWF, Syntilo 1601, was reformulated with TEA, isononanoic acid, neodecnoic acid, Cobratec TT50S, and pluronic 17R40, which were resistant to biological treatment. Although, no change in the overall oxidation state of the MWF, metabolic activity did occur as breakdown products were observed. This suggested that both raw materials and metabolic breakdown products were recalcitrant. Thus, immobilisation agents were applied to aid further biodegradation by removing toxic bottleneck compounds. It was found that hybrid nano-iron and kaffir lime leaf performed similarly in removing chemical oxygen demand and ammonium from the system. Work in this Thesis demonstrated that the combined use of biological treatment and immobilisation agents effectively overcome the limitations of biological treatment alone by removing bottleneck compounds, which allowed greater COD reduction. This laboratory scale is a proof of principle, which needs to be tested at full scale.